Evaluasi Keamanan Sirup Batuk Anak Melalui Deteksi Dietilen Glikol: Safety Evaluation of Children's Cough Syrup Through Detection of Diethylene Glycol - Andi Ardiansyah Arifin; Megawati; Nurjannah; Nur, Syamsu (Jurusan Farmasi Poltekkes kemenkes Makassar, 2025)
A recent report highlighted cases of contamination in children's cough syrup containing diethylene glycol, which poses potential health risks for children. This study aims to identify the presence of diethylene glycol in various children's cough syrups sold in Makassar City using Thin Layer Chromatography (TLC) and FT-IR Spectroscopy methods. A total of 9 samples of children's cough syrup from three different brands, each originating from three batches, were analyzed in this study. The TLC analysis results showed significant differences between the samples and the standard. The Rf values of the samples ranged from 0.72 to 0.85, while the Rf value of the diethylene glycol standard was recorded at 0.41. Additionally, FT-IR analysis, based on the wave numbers and intensity of the spectra, indicated that the sample spectra did not match those of the diethylene glycol standard. Based on the evaluation of all children's cough syrup samples using these two methods, no profiles consistent with the characteristics of diethylene glycol were detected.